Computational investigation of the Mycobacterium tuberculosis catalase-peroxidase (katG) dependent activation of isoniazid - Reyes, Yves Ira A. (Animo Repository, 2019)
Tuberculosis (TB) has been one of the deadliest global epidemics throughout history. Isoniazid or isonicotinyl hydrazide (INH) is one of the most efficient drugs used to treat TB. INH is a prodrug that is thought to be activated by its reaction with the catalase-peroxide (katG) enzyme of Mycobacterium tuberculosis (M. tb), the bacterial pathogen that causes TB. However, there is no consensus on the exact mechanism of M. tb, katG dependent activation of INH and different studies lead to different theories. One of the theories is that INH binds near the heme cofactor of the enzyme to react with the two-electron oxidized oxyferryl heme intermediate compoundI (CpdI). Therefore, this study confirms this theory through the application of density functional theory calculations. INH was docked to katG and the best pose (-6.8 kcal/mol) was found to bind at the distal side of the heme cofactor in contact with the heme along with seven highly conserved amino acid residues to form hydrogen bonds except for Ile228 which exhibited the weakest interaction (-13.78 kcal/mol). The strongest interactions with INH were calculated for Agr104 (-39.64 kcal/mol) and Asp137 (-32.85 kal/mol). Molecular electrostatic potential surfaces revealed complementary dipole interactions between residues and INH. Frontier molecular orbitals and population analyses revealed that INH generally lost electron density because of orbitals that had more density in the RES molecule. Simulation pf CpdI models with varying set of atoms present on the proximal side ta the UB3LYP/6-31lg(d)/lanl2dz level of theory revealed impact of the Trp321 on the electronic properties of the heme. Without the Trp321 the heme assumed a triradical state with single electrons on Ï€xz and Ï€yz orbitals of Fe and another on the aâ‚‚u orbital of the porphyrin ring that can either be coupled with the first two, to form a high spin state, or decoupled to form a low spin state. With Trp 321, however, a transfer of an electron from Ï€Trp orbital to aâ‚‚u porphy